ETHNOMATHEMATICAL ANALYSIS ON TRADITIONAL SNACKS AT THE ELEMENTARY SCHOOL LEVEL - Karmila, Uvi; Sajiman, Supardi Uki (Journal of Higher Education and Academic Advancement, 2025)
Objective:  This study aims to describe the use of traditional snacks as a mathematics learning medium based on ethnomathematics in elementary schools. Method: This study uses a qualitative descriptive approach with ethnographic methods. Data was obtained through exploration, documentation, and literature review of various types of traditional snacks that have a shape that resembles a flat shape, such as cucur cake (circle), lupis cake (triangle), layer cake (rectangular), and talam cake (square). Results: The results of the study show that traditional snacks can be used as contextual media in learning flat building geometry, so that it can increase students' interest and understanding of mathematics materials. Novelty: The integration of local culture in mathematics learning not only provides a meaningful learning experience, but also preserves local wisdom in the educational process.